Kendala Dalam Pengembangan Ekowisata Di Desa Selumbung, Kecamatan Manggis, Kabupaten Karangsem - I Made Abdi Swabawa; I Nyoman Sukma Arida (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2022)
One of the disposed in development of global tourism nowdays is powerful of phenomenon to traveled back tonature. Selumbung Village is a village that has potential to be developed into a tourist visiting area based onecotourism. The purpose of this research is to identify the potential of ecotourism that can be used as touristattractions and constraints of ecotourism development in Selumbung Village. Data collection techniques used in thisresearch is observation, interviews, and documentation. ques. The determination technique of informant uses in thisresearch is a purposive sampling. The data analysis technique used in this research is a qualitative data analysistechnique. Selumbung Village located in Karangasem Regency has a lot of natural potential that can be developedinto ecotourism. The potential of Selumbung Village is two waterfalls, cocoa plantations, a place of makingsculptures, beekeeping and a place for making wood carvings. There are obstacles faced in developing ecotourism inSelumbung Village, including facilities and infrastructure, promotional media to inform about the potential of nature,culture, local wisdom, and lack of understanding for local communities in managing existing resources. These factorsare a problem for the development and management of ecotourism in Selumbung Village.Keyword: Potency, development, ecotourism